Level of consumer awareness and acceptability on the quality of counterfeit branded tee shirt - Del Rosario, Anna Marie T.; Florendo, Raquel Baltazar (1998.)
The research aims to determine the level of consumer awareness and acceptability on the quality of counterfeit branded tee shirts. A total of 100 college students of the University of the Philippine - Diliman from 10 colleges with a population of more than 500 were selected randomly. There were two instruments used to collect data. The first one was the application of a normative survey in a form of questionnaire. The second instrument is an interview survey form with an aid of concrete samples of an identical and imitation tee shirt. Results of the study showed that there are three general attributes of quality that consumers consider most. First is fabric quality followed by fit and thirdly is durability. Though not a majority percentage of the respondents patronized imitations, low price of imitations proved to have strongest influence that drive consumers to buy. Next to price that induces consumers to buy is the quality. Findings for the second method implied that consumers could not identify original from imitation. They used no standard measure in their judgement. Conception then of quality is based only on assumptions and not on objective knowledge.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Consumer behavior -- Philippines